Disclosure of accountability information in Public Sector Annual Report : the case of Malaysian Federal Statutory Bodies / Nur Barizah Abu Bakar - Abu Bakar, Nur Barizah (2013)
Various accountability issues concerning the Malaysian Federal Statutory Bodies (MFSB) have been revealed by various parties in their reports. Being a public sector body adopting a corporate-styled management and representing a substantial segment of the public sector, MFSB are expected to discharge its accountability and promote transparency. One aspect of accountability and transparency is the disclosure of accountability information (AI) in the annual report. In light of this, the study seeks to obtain insights on the extent of disclosure of AI in the annual reports of MFSB. Drawing from the public accountability paradigm and institutional theory, three objectives of the study are developed: (i) to determine the extent of disclosure of AI in MFSB annual reports, (ii) to examine whether certain set of variables, namely the type of MFSB, board size, board composition, existence of audit committee and fiscal stress have significant association with the extent of disclosure as found in (i), and (iii) to identify the reasons for disclosure (and nondisclosure) of AI in MFSB annual reports. The study employs a mixed method research design. The data for quantitative phase was collected from 2008 annual reports of 106 MFSB using a disclosure index. They were then analysed using the General Linear Model (GLM) command for the multiple regression technique. Thereafter, 20 semi-structured interviews were conducted with 32 preparers and/or managers of MFSB and the meaning categorization approach was employed to analyse the data. It was found that MFSB provided a moderate level of disclosure of 47.8 per cent in their annual report, ranging from 25 to 71 per cent. The results also showed that the most disclosed category was Performance, followed by the Overview, Financial, Others (i.e. human resource, socio-environmental and main assets), and Governance category. In addition, the study found that the strength of the regression model is moderate at an adjusted R2 of 0.409. Two out of five hypotheses are supported. It was established that there is a significant association between the extent of AI disclosure and the type of MFSB as well as a significant positive association between the extent of AI disclosure and the existence of an internal member on the board. The interview revealed 53 and 58 reasons for disclosure and nondisclosure, respectively. Six themes emerged from both situations with three of them being similar, namely the nature of the data for reporting, implication of reporting, and traditions and practices in preparing reports. The themes unique in the case of disclosure are external influences, internal influences, and awareness. Among the common reasons for disclosure are to adapt the reporting practices of others and to enlighten stakeholders on MFSB functions and activities. On the other hand, the three unique themes for nondisclosure are demand of the information, resources, and preparers. The main reasons for nondisclosure is the lack of reporting benefit and insignificant data. The study provides useful inputs for both practitioners and researchers which may subsequently help to improve the extent of disclosure of AI and eventually enhance accountability and transparency among public sector entities particularly MFSB.